Inhibition of the glucose transporter SGLT2 with dapagliflozin in pancreatic alpha cells triggers glucagon secretion - Bonner, Caroline; Kerr-Conte, Julie; Gmyr, Valéry; Queniat, Gurvan; Moerman, Ericka; Thévenet, Julien; Beaucamps, Cédric; Delalleau, Nathalie; Popescu, Iuliana; Malaisse, Willy J; Sener, Abdullah; Deprez, Benoit; et al. (Nature medicine, 2015)
The recently approved drug dapagliflozin is now shown to increase glucagon secretion by acting on pancreatic alpha cells, which has implications for the potency of its antidiabetic effects Type 2 diabetes (T2D) is characterized by chronic hyperglycemia resulting from a deficiency in insulin signaling, because of insulin resistance and/or defects in insulin secretion; it is also associated with increases in glucagon and endogenous glucose production (EGP) 1 . Gliflozins, including dapagliflozin, are a new class of approved oral antidiabetic agents that specifically inhibit sodium-glucose co-transporter 2 (SGLT2) function in the kidney 2 , 3 , 4 , 5 , thus preventing renal glucose reabsorption and increasing glycosuria in diabetic individuals while reducing hyperglycemia. However, gliflozin treatment in subjects with T2D increases both plasma glucagon and EGP 6 , 7 by unknown mechanisms. In spite of the rise in EGP, T2D patients treated with gliflozin have lower blood glucose levels than those receiving placebo, possibly because of increased glycosuria 6 , 7 ; however, the resulting increase in plasma glucagon levels represents a possible concerning side effect, especially in a patient population already affected by hyperglucagonemia. Here we demonstrate that SGLT2 is expressed in glucagon-secreting alpha cells of the pancreatic islets. We further found that expression of SLC5A2 (which encodes SGLT2) was lower and glucagon ( GCG ) gene expression was higher in islets from T2D individuals and in normal islets exposed to chronic hyperglycemia than in islets from non-diabetics. Moreover, hepatocyte nuclear factor 4-α (HNF4A) is specifically expressed in human alpha cells, in which it controls SLC5A2 expression, and its expression is downregulated by hyperglycemia. In addition, inhibition of either SLC5A2 via siRNA-induced gene silencing or SGLT2 via dapagliflozin treatment in human islets triggered glucagon secretion through K ATP channel activation. Finally, we found that dapagliflozin treatment further promotes glucagon secretion and hepatic gluconeogenesis in healthy mice, thereby limiting the decrease of plasma glucose induced by fasting. Collectively, these results identify a heretofore unknown role of SGLT2 and designate dapagliflozin an alpha cell secretagogue.